Anastrepha spp. (Diptera: Tephritidae) in Ximenia americana and other tropical fruits in a Brazilian savannah - Araújo, Almerinda Amélia Rodrigues; Araújo, José Ribamar Gusmão; Lemos, Raimunda Nonata Santos de; Silva, Paulo Roberto Ramalho; França, Solange Maria; Soares, Lízio Laguna; Santos, Anne Caroline Bezerra dos; Mesquita, Mário Luiz Ribeiro (Journal of Agricultural Studies, 2021)
The aim of this work was to evaluate the infestation of Anastrepha species in several fruit tree species and A. alveata in wild plum Ximenia americana L. (Olacaceae), as well as the fruit fly community in a Savannah area using faunal indexes and population fluctuation. For this, we installed McPhail traps and carried out collections at Palmeiras home garden, municipality of São Pedro of Piauí, state of Piaui, northeastern Brazil. We noted high infestation of A. alveata in wild plum, with 144.2 puparia/kg, 216.1 puparia/kg and 321.6 puparia/kg for the years 2014, 2015 and 2016. The infestation indexes of A. obliqua in red mombin (Spondias purpurea) were 146.1 puparia/kg in 2016 and 479.2 puparia/kg in 2017, and in umbu-hog plum (Spondias sp.) 607.3 puparia/kg in 2017, both from the Anacardiaceae family. The species that composed the fruit fly community were A. alveata, A. ethalea (predominant), A. obliqua, A. zenildae (dominant and accessory), A. sororcula, A. fraterculus and Anastrepha sp. (accidental). The population fluctuation of A. ethalea occurred from March to October, while A. alveata presented population peaks in the fruiting of wild plum, between October and December